Contemporary arabic writers and cultural globalisation: religious symbolism - Abumalham, Montserrat (Anaquel de Estudios Árabes, 2004)
Globalisation and localisation are opposite poles of an identitary paradoxe. In Modern Arabic Literature we can find all kind of universal myths and symbols taken from inner as well as from outer traditions used like materials to build a separate identity.